Seismic assessment of a reconstructed historic masonry structure: A case study on the ruins of Bigali castle mosque built in the early 1800s - Güneş, Barış; Coşgun, Turgay; Sayın, Barış; Ceylan, O?uz; Mangır, Atakan; Gümüşdağ, Gökhan (Elsevier Ltd, 2021)
Architectural and cultural heritage structures that have provided important services in the past may lose their functions over time and become out of service due to possible reasons. The loss of the structural integrity in these structures is mostly connected to the material damages due to long-term exposure to environmental conditions and human intervention. Despite the negative period that these structures have been faced with since they are out of service, they need to be protected due to their historical importance and cultural identity. Therefore, the survival of the heritage of these structures can be possible through on-site observations and subsequent analysis and restoration/reconstruction process. This paper focuses on the seismic assessment of a reconstructed historic ruined mosque located in a castle constructed between 1807 and 1820. The study consists of four stages: on-site examinations, laboratory tests, reconstruction process and seismic performance analyses of the examined structure. The field study involves the visual inspection of structural deterioration and gathering of representative samples from various parts of the structure. The laboratory study includes mechanical, chemical and mineralogical analyses of the samples obtained from the structure. Reconstruction process of the mosque considering its original form are presented in the third stage. Finally, the seismic performance level of the structure against seismic effects is determined by performing linear, pushover and kinematic analyses. The presentation of the processes within this study on the reconstruction of the structural integrity of a historic structure that has suffered from deterioration over time into its original form will add valuable information to the literature. The adopted methodology and presented findings can be used as a guide for similar studies from a geometric and material point of view. All of the essential steps used for the reconstruction of the originality of the structure including obtaining the data related to the history of the structure, field studies, laboratory tests, numerical analyses, and the stages of the reconstruction process are presented on an example case study.
Keywords: Masonry Ruin; Cultural Heritage; Reconstruction; Field Study; Lab Test; Linear Analysis; Pushover Analysis; Kinematic Analysis